2012
DOI: 10.1007/s10165-012-0678-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results of alendronate monotherapy and combined therapy with menatetrenone (VitK2) in postmenopausal RA patients

Abstract: Combined therapy with alendronate and VitK2 decreases bone metabolism marker levels and serum ucOC levels, and increases lumbar spine and femoral neck bone density in postmenopausal RA patients with abnormal ucOC levels and osteoporosis or osteopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Однако в недавнем рандомизированном контролируемом исследовании популяции постменопаузальных китайских женщин средних лет и в пожилом возрасте дополнительное добавление к витамину K 2 в дозе 90 мкг в день препаратов кальция (500 мг в день) и витамина D (в дозе 400 МЕ НАУЧНЫЙ ОБЗОР в день) не показало улучшения эффекта в сравнении с монотерапией витамином K 2 [44]. Единичные исследования применения витамина K 2 с антирезорбтивными препаратами, в частности с бисфосфонатами, также продемонстрировали неоднозначные результаты: так, комбинация с алендронатом была ассоциирована с повышением МПКТ в бедренной кости у женщин с постменопаузальным остеопорозом [45], в то время как комбинированная терапия с ризедронатом не показала эффективности по сравнению с монотерапией ризедронатом [46].…”
Section: влияние витамина K 2 на костную тканьunclassified
“…Однако в недавнем рандомизированном контролируемом исследовании популяции постменопаузальных китайских женщин средних лет и в пожилом возрасте дополнительное добавление к витамину K 2 в дозе 90 мкг в день препаратов кальция (500 мг в день) и витамина D (в дозе 400 МЕ НАУЧНЫЙ ОБЗОР в день) не показало улучшения эффекта в сравнении с монотерапией витамином K 2 [44]. Единичные исследования применения витамина K 2 с антирезорбтивными препаратами, в частности с бисфосфонатами, также продемонстрировали неоднозначные результаты: так, комбинация с алендронатом была ассоциирована с повышением МПКТ в бедренной кости у женщин с постменопаузальным остеопорозом [45], в то время как комбинированная терапия с ризедронатом не показала эффективности по сравнению с монотерапией ризедронатом [46].…”
Section: влияние витамина K 2 на костную тканьunclassified
“…RA increases the risk of osteoporosis and fractures which may also be associated with secondary osteoporosis caused by glucocorticoid therapy. Early prevention of osteoporosis is, therefore, important to prevent fractures and to improve quality of life and life expectancy [5]. Previous clinical studies indicated that vitamin K 2 (menatetrenone) effectively prevents fractures and sustains lumbar bone mineral density in osteoporosis [6].…”
Section: Introductionmentioning
confidence: 99%